2003
DOI: 10.1074/jbc.m307620200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the Mitochondrial Translation System during Terminal Differentiation of HL-60 cells by 12-O-Tetradecanoyl-1-phorbol-13-acetate

Abstract: Mitochondrial (mt) biogenesis depends on both the nuclear and mt genomes, and a coordination of these two genetic systems is necessary for proper cell functioning. Little is known about the regulatory mechanisms of mt translation or about the expression of mt translation factors. Here, we studied the expression of mt translation factors during 12-O-tetradecanoyl-1-phorbol-13-acetate (TPA)-induced terminal differentiation of HL-60 cells. For all mt translation factors investigated, mRNA expression was markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In addition, the mitochondria contain about 1000 kind of proteins, more than 98% of them are encoded by nuclear DNA, and they are synthesized in the cytoplasmic ribosomes, then transported to the mitochondria and sorted and located in various parts, this process is important to maintain the steady-state mitochondrial functions. It has been reported that in the 12-O-Tetradecanoyl-1-phorbol-13-acetate (TPA) -induced differentiation of HL-60 cells, the mitochondrial transport system was down-regulated [47]. Our research found that PMA treatment down-regulate the expression levels of Tim9 and Tim10 proteins.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, the mitochondria contain about 1000 kind of proteins, more than 98% of them are encoded by nuclear DNA, and they are synthesized in the cytoplasmic ribosomes, then transported to the mitochondria and sorted and located in various parts, this process is important to maintain the steady-state mitochondrial functions. It has been reported that in the 12-O-Tetradecanoyl-1-phorbol-13-acetate (TPA) -induced differentiation of HL-60 cells, the mitochondrial transport system was down-regulated [47]. Our research found that PMA treatment down-regulate the expression levels of Tim9 and Tim10 proteins.…”
Section: Discussionsupporting
confidence: 49%
“…PMA has been reported to regulate gene expression by transcriptional as well as post-transcriptional mechanisms. For example, the induction of VEGF by PMA in human keratinocytes depends on an AP-1 binding site in its promoter flanking region of the VEGF gene [49] while it regulates the expression of mitochondrial elongation factor Tu in HL60 cells at the level of RNA stability [50]. Our results show that PMA does not induce ANGPTL4 expression by increasing the stability of its respective mRNA.…”
Section: Discussionmentioning
confidence: 72%
“…The translational controls were evaluated by sedimentation experiments. For this, mRNAs were extracted for every fraction of either sub-polysomes or polysomes (Figure 3A) before and after the TPA treatment in human HL-60RG cells (23) and the relative abundance of them was detected by semi-quantitative real-time PCR. Before the sedimentation experiment, the RNA levels (transcription level) of all 239 genes with and without TPA treatment (TPA+/TPA-) were measured by real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…We used exactly the same methods and samples as those previously reported (23). Namely, HL-60 rapid growth cell (RG) derived from HL-60 cell lines was cultured.…”
Section: Methodsmentioning
confidence: 99%